Identification of New Prognostic Markers and Therapeutic Targets for Non-Muscle Invasive Bladder Cancer: HER2 as a Potential Target Antigen - Chae, Han Kyu; Nam, Wook; Kim, Han Gwun; Lim, Sharon; Noh, Byeong-Joo; Kim, So Won; Kang, Gil Hyun; Park, Jong Yeon; Eom, Dae-Woon; Kim, Sung Jin (Frontiers in Immunology, 2022)
Bacillus Calmette–Guérin (BCG) is the gold standard adjuvant treatment for non-muscle-invasive bladder cancer (NMIBC). However, given the current global shortage of BCG, new treatments are needed. We evaluated tumor microenvironment markers as potential BCG alternatives for NMIBC treatment. Programmed death-ligand 1, human epidermal growth factor receptor-2 (HER2), programmed cell death-1 (PD1), CD8, and Ki67 levels were measured in treatment-naïve NMIBC and MIBC patients (pTa, pT1, and pT2 stages). Univariate and multivariate Cox proportional hazard models were used to determine the impact of these markers and other clinicopathological factors on survival, recurrence, and progression. EP263, IM142, PD1, and Ki67 levels were the highest in the T2 stage, followed by the T1 and Ta stages. HER2 and IM263 expressions were higher in the T1 and T2 stages than in the Ta stage. In NMIBC, the significant prognostic factors for recurrence-free survival were adjuvant therapy, tumor grade, and HER2 positivity, whereas those for progression-free survival included age, T-stage, and IM263. Age, T-stage, EP263, PD1, CD8, and Ki67 levels were significant factors associated with overall survival. IM263 and HER2 are potential biomarkers for progression and recurrence, respectively. Therefore, we propose HER2 as a potential target antigen for intravesical therapeutics as a BCG alternative.